Bioinspired periodic mesoporous tin oxides enable steady nonequilibrium chemical sensing for enhanced gas discrimination - Keyu Chen; Yu Deng; Tianming Hu; Jichun Li; Xin-Yu Huang; Chengcheng Zhu; Honggang Chen; Meihua Chen; Limin Wu; Yonghui Deng; Wenhe Xie (Proceedings of the National Academy of Sciences, 2026)
Periodic porous structures with interconnected pore channels and high specific surface area are widely spread in natural world. These structures guarantee rapid mass transportation and efficient biochemical reactions within organisms, thereby satisfying the requirements of complex life activities. Inspired by the periodic porous membrane and breathing process of the mammalian respiratory system, a steady nonequilibrium chemical sensing process is established to achieve high-accuracy gas discrimination based on artificial periodic porous structures consisting of metal oxide semiconductors and pulse heating (PH) technique. Owing to its highly accessible mesopores and enormous solid–gas interfaces, periodic mesoporous tin oxide (P-mSnO 2 ) facilitates gas diffusion during PH cycles and enhances the catalytic reaction between gas molecules and P-mSnO 2 . As a result, the P-mSnO 2 based sensor exhibits stable and enhanced overshoot peaks in gas sensing response curves, thus achieving superior discrimination accuracy (99.8%) for six gases under the assistance of convolutional neural network (CNN). Furthermore, the mechanism underlying the distinct shapes of the gas response curves is uncovered, revealing that gas adsorption capacity, gas diffusion coefficient, catalytic reaction barrier, and transferred electron numbers are crucial factors. This work lays the foundation for the development of single-sensor artificial olfactory intelligence and the exploration of periodic porous structures in diverse frontier fields.